2017
DOI: 10.1007/s00408-017-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax After Transbronchial Biopsy in Pulmonary Fibrosis: Lessons from the Multicenter COMET Trial

Abstract: Purpose Some patients with diffuse interstitial lung disease (ILD) undergo bronchoscopy with transbronchial biopsy (TBB) as part of their diagnostic evaluation. It is unclear what the incidence and risk factors for pneumothorax (PTX) following TBB are in this patient population. Methods Ninety-seven subjects with pulmonary fibrosis who underwent a research bronchoscopy with TBB as part of the multicenter Correlating Outcomes with Biochemical Markers to Estimate Time-progression in Idiopathic Pulmonary Fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
10
1
2
Order By: Relevance
“…In our study, the incidence of PTX was 6.16% which is comparable to the data from the BTS guideline (PTX incidence reported to be 1–6%) [3], the Sindhwani et al study (10.2%) [8], from the COMET Trial (7.2%) [9] and from the Ibrahim et al study (9.8%) [10]. Our cohort included 48% of patients with nodular lesions and there was an insignificant trend towards more nodular lesions TBB in the PTX group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, the incidence of PTX was 6.16% which is comparable to the data from the BTS guideline (PTX incidence reported to be 1–6%) [3], the Sindhwani et al study (10.2%) [8], from the COMET Trial (7.2%) [9] and from the Ibrahim et al study (9.8%) [10]. Our cohort included 48% of patients with nodular lesions and there was an insignificant trend towards more nodular lesions TBB in the PTX group.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, compared to patients without PTX, in patients with PTX there was also an insignificant trend towards more pulmonary emphysema in our cohort. The ideal number of TBB samples that should be taken at each procedure remains controversial, some authors concluded that it has no relevance to risk of post-procedural PTX [9]. In our analysis, the number of samples taken during TBB was significantly associated with PTX development and remained a significant factor of PTX development also in the logistic regression analysis.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…By achieving a reliable diagnosis based on imaging features, patients potentially avoid the risks of bleeding and general anesthesia and the high costs associated with a surgical biopsy [13][14][15][16]. Although UIP and NSIP imaging features have been described extensively in the literature and were incorporated in the diagnostic guidelines, no systematic review of the literature has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…in this issue highlights the clinical relevance of another well known, but poorly reported complication of IPF, namely the appearance of a secondary spontaneous pneumothorax (SSP) . Needless to say, pneumothorax in this population may also follow a transbronchial lung biopsy (incidence of 7.2% in a recent study), but data regarding the prognostic influence of iatrogenic pneumothorax on IPF outcome are lacking. The pathogenesis of SSP in the context of IPF is uncertain.…”
mentioning
confidence: 98%